Use of Interactive Learning Media to Improve Student Learning Outcomes in Pneumatic Subject Matter Electronic Control System - Agus Hariyanto; Rufii Rufii (Universitas Negeri Semarang, 2024)
Learning Media is a learning tool used by someone using tools created to make it easier to deliver material when teaching at school. Based on observations made by the teacher, the findings were: (a) there were 12 students out of a total of 29 who had not yet reached the KKM; Students' interest in learning is lacking, students look less enthusiastic when the teacher explains the material presented. Based on the description above, the author wishes to examine this problem, through research with the title